2022
DOI: 10.3389/fgene.2022.834111
|View full text |Cite
|
Sign up to set email alerts
|

Differently Expressed Circular RNAs in Lacrimal Sacs From Patients With Chronic Dacryocystitis

Abstract: This study was designed to identify differently expressed circular RNAs (circRNAs) and investigate their potential roles in lacrimal sacs from patients with chronic dacryocystitis. The lacrimal sac samples of three chronic dacryocystitis patients and three control subjects were collected for RNA sequencing after ribosomal RNA was depleted. Differently expressed circRNAs and messenger RNAs (mRNAs) were used for co-expression analysis. CircRNA-microRNA (miRNA)-mRNA interaction network were also established by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Nasolacrimal duct obstruction is the most important cause of dacryocystitis [ 14 ]. Obstruction of the lower lacrimal system causes tear discharge disorders that allow bacteria to multiply, leading to lacrimal sac inflammation, which further aggravates nasolacrimal duct obstruction, creating a vicious cycle [ 15 17 ]. An epidemiological survey of dacryocystitis by Khatoon et al showed that secondary nasolacrimal duct obstruction accounted for approximately 3.78% of cases, much less than primary nasolacrimal duct obstruction (96.23%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nasolacrimal duct obstruction is the most important cause of dacryocystitis [ 14 ]. Obstruction of the lower lacrimal system causes tear discharge disorders that allow bacteria to multiply, leading to lacrimal sac inflammation, which further aggravates nasolacrimal duct obstruction, creating a vicious cycle [ 15 17 ]. An epidemiological survey of dacryocystitis by Khatoon et al showed that secondary nasolacrimal duct obstruction accounted for approximately 3.78% of cases, much less than primary nasolacrimal duct obstruction (96.23%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…After screening high confidence miRNA-mRNA relationships, we created a network map. To calculate the sequence binding sites and energies of these miRNA-mRNAs, we utilized MiRanda 3.3a …”
Section: Methodsmentioning
confidence: 99%
“…To calculate the sequence binding sites and energies of these miRNA-mRNAs, we utilized MiRanda 3.3a. 21 …”
Section: Methodsmentioning
confidence: 99%